1985
DOI: 10.1159/000128493
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Response of Elderly Patients Undergoing Major Surgery under Moderate Normovolemic Hemodilution

Abstract: Moderate normovolemic hemodilution (MNH) is used in general surgery not only when major blood loss is anticipated but also as a prophylactic measure for the prevention of postoperative deep vein thrombosis. The hemodynamic effects of MNH (hematocrit value 27–29%) with dextran 70 as diluent were evaluated in 50 patients undergoing major surgery (cholecystectomy or total hip arthroplasty).They were divided into two groups according to age: I < 60; II > 60 years. Comparison of the results obtained in the two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
3

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 6 publications
0
12
0
3
Order By: Relevance
“…This hypothesis is substantiated in the present study in that only patients in sinus rhythm showed an increase in mean pulmonary artery pressure and only in these patients was an increase in PaO 2 observed. Unchanged [4,9,13] as well as decreased pulmonary vascular resistance [14,15] have been described during haemodilution. However, the reason why, in contrast to systemic vascular resistance, pulmonary vascular resistance did not decrease in the present study remains unclear.…”
Section: R Spahn Et Al • Haemodilution Tolerancementioning
confidence: 99%
“…This hypothesis is substantiated in the present study in that only patients in sinus rhythm showed an increase in mean pulmonary artery pressure and only in these patients was an increase in PaO 2 observed. Unchanged [4,9,13] as well as decreased pulmonary vascular resistance [14,15] have been described during haemodilution. However, the reason why, in contrast to systemic vascular resistance, pulmonary vascular resistance did not decrease in the present study remains unclear.…”
Section: R Spahn Et Al • Haemodilution Tolerancementioning
confidence: 99%
“…Only patients ASA I or II to tolerate deep hemodilution (20%) were selected. Age was not a limiting factor for the selection, since even patients older than 60 years could tolerate this procedure 17 . Patients with higher weight required removal of a greater volume of blood to achieve the desired hematocrit.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, small studies have shown that elderly individuals tolerate hemodilution to a hematocrit less than 30%. 13 In addition, the results of the TRICC trial did not demonstrate a difference in mortality for patients over the age of 55 yr who were transfused at a hemoglobin concentration of 70 g·L -1 compared to a hemoglobin concentration of less than 100 g·L -1 . 7 Yet, it is well reported that age is a risk factor for transfusion.…”
mentioning
confidence: 96%
“…En effet, de petites études ont montré que les gens âgés tolèrent l'hémodilution à un hématocrite de moins de 30 %. 13 De plus, les résultats de l'étude TRICC n'ont pas montré de différence de mortalité chez les patients de plus de 55 ans transfusés à une concentration d'hémoglobine de 70 g·L -1 comparée à une concentration de moins de 100 g·L -1 . 7 Mais il est bien prouvé que l'âge est un facteur de risque pour la transfusion.…”
unclassified